Surface roughness and surface integrity of end milled titanium alloy TI-6AL-4V at room temperature and preheated machining - Ginta, Turnad Lenggo; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Lajis, M. A. (2009)
This paper is concerned with the surface roughness and surface integrity of titanium alloy Ti- 6AI-4V after end milling under room temperature and preheated conditions. End milling experiments were carried out on a Vertical Machining Centre, using 20 mm uncoated WC-Co inserts. High frequency induction heating was utilized for preheated experiments. Surface roughness values were measured using a surface roughness measuring instrument Mitutoyo Surftest Model SV-500. The surface integrity and subsurface alteration were investigated by employing scanning electron microscope and Vickers micro-hardness. Prior to surface integrity inspections, the sample was cut with electro discharge wire cutting, then mounted using hot mounting, ground using silicon carbide papers, polished with alumina solution, and then etched with 10% HF, 5% HN03 and 85% H20 solutions. Microhardness was measured along the depth (perpendicular to the machined surface) at an interval of 0.01 mm starting from the top surface up and continued up to a depth of 0.5 mm. The results show that the surface layer could be divided into three zones, namely heat affected zone (Zone I), strain hardened zone (Zone II), and the base material (Zone III). A higher surface roughness achieved in preheated machining is attributed to the development of built-up edge (BUE) on the cutting tool surface.